Pathophysiological Characteristics of Phlegm-stasis Cementation Syndrome in Coronary Heart Disease: a Review and Update - Jian-Xun Ren; Dennis Chang; Jian-Xun Liu (World Journal of Traditional Chinese Medicine, 2016)
The pathophysiological characteristics of Phlegm-stasis Cementation Syndrome in Coronary Heart Disease (CHD) has been summarized in this article. According to epidemiological investigations, phlegm-stasis cementation syndrome has become a dominant syndrome in CHD along with the improvement in living and dietary condition. The interaction between blood stasis and phlegm turbidity that is called Phlegm-stasis Cementation Syndrome exists in CHD and other diseases. The bridge linked blood stasis and phlegm turbidity lies in the adversely effects of lipid metabolism disorder on platelet activation, vascular function and hemorheology indexes. Lipid metabolism disorder also can induce persistent inflammation including monocyte/macrophage activation and oxidative stress. Inflammation also is an important stimulating factor for atherosclerosis and the biology that underlies the complications of CHD, which belonged to the concept of “toxin” in Traditional Chinese medicines (TCM). On the other hand, the important function of inflammatory process on abnormal hemorheology, platelet activation and vascular dysfunction can be used to elucidate the basic pathogenetic condition of the toxin inducing blood stasis in TCM. Therefore, it is this pathological process that can be used to address the basic pathogenetic theory of phlegm turbidity inducing the symptom of toxin and blood stasis, and subsequently phlegm-stasis cementation in TCM. We deduced that lipid metabolic disturbance, inflammation activation, vascular dyfunction and hemorheological disorders could be as pathophysiological characteristics of Phlegm-stasis cementation syndrome.